Description Of The Teaching Readiness Of PGSD UBT Students In Review From Self Efficacy - Dinda Risky Ramona; Desy Irsalina Savitri; Oriza Zativalen (Universitas Muhammadiyah Lamongan, 2025)
This research describes the level of teaching readiness in IPAS (Integrated Science and Social Science) of PGSD UBT (Elementary Teacher Education) students as viewed from self-efficacy. Introduction and research objective: introduction and research objective: state briefly the problem or issue addressed and the research goal, method: This study applies a mixed-methods approach. The sample used in this study consists of PGSD UBT students who have undergone the PPL (Field Experience Program). The research sample involves 40 students, and the method used for sampling is total sampling. The tools used for data collection include self-efficacy, questionnaires and interview guidelines. Based on data analysis, the teaching readiness of IPAS students in terms of self-efficacy shows a high result, with an average percentage of 62.91% in the high category and 37.08% in the medium category. results: This percentage is based on six indicators of student self-efficacy, namely: (1) Confidence in facing challenging teaching tasks reaches 50% in the high category and 50% in the medium; (2) Confidence in planning IPAS teaching is 65% high and 35% . Currently; (3) Confidence in facing various situations while teaching IPAS is 65% high and 35% moderate; (4) Confidence in anticipating new teaching situations is 72.5% high and 27.5% moderate; (5) Resilience in facing difficulties while teaching IPAS is 62.5% high and 37.5% moderate; and (6) Persistence in overcoming challenges in teaching IPAS is 25 (62.5%) high and 15 (37.5%) moderate. Thus, it can be concluded that the readiness to teach IPAS of UBT PGSD students in terms of self-efficacy is in the high category.